1996
DOI: 10.1007/s002040050279
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury transport across the placenta via neutral amino acid carrier

Abstract: Methylmercury (MeHg) penetrates the placental barrier to affect developing fetuses in the uterus. However, the mechanism of placental MeHg transport is not well defined. To clarify the MeHg transport system that functions in the placenta, pregnant rats were intravenously administered MeHg on day 18 of gestation. The fetal blood was collected from the umbilical cord at 30 and 60 min after the administration, and its mercury concentration was measured. MeHg was found to be rapidly transported to the fetal blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(94 citation statements)
references
References 12 publications
6
86
1
1
Order By: Relevance
“…The above T-Hg c : T-Hg m and MeHg c : MeHg m ratios are almost consistent with the number-weighted ratios estimated with use of the meta-analysis from ten selected studies, that is, 1.51 for T-Hg and 1.89 for MeHg (Stern and Smith 2003). Also, MeHg distributes to all tissues readily crossing the blood-brain and placenta barriers (Aschner and Clarkson 1988;Kajiwara et al 1996). In addition to the hypersusceptibility of the developing brain, these fi ndings have the cogency to explain the fact that mothers who bore children with congenital Minamata disease did not have more severe clini- cal symptoms or signs than did patients with acquired Minamata disease (Arima 1979).…”
Section: Mercury Concentrations In Cord Bloodsupporting
confidence: 82%
“…The above T-Hg c : T-Hg m and MeHg c : MeHg m ratios are almost consistent with the number-weighted ratios estimated with use of the meta-analysis from ten selected studies, that is, 1.51 for T-Hg and 1.89 for MeHg (Stern and Smith 2003). Also, MeHg distributes to all tissues readily crossing the blood-brain and placenta barriers (Aschner and Clarkson 1988;Kajiwara et al 1996). In addition to the hypersusceptibility of the developing brain, these fi ndings have the cogency to explain the fact that mothers who bore children with congenital Minamata disease did not have more severe clini- cal symptoms or signs than did patients with acquired Minamata disease (Arima 1979).…”
Section: Mercury Concentrations In Cord Bloodsupporting
confidence: 82%
“…However, because Hg 2+ seems to cross the placental barrier only at high concentrations (14,29), most I-Hg likely passed to the fetus in the form of Hg 0 . MeHg has been proposed to be readily transported across the placenta bound to thiol-groups in cysteine, thereby mimicking methionine (32). Indeed, we found higher MeHg concentrations in umbilical cord blood than in maternal blood.…”
Section: Discussionmentioning
confidence: 55%
“…Yet, little is known about the mechanism(s) by which this metal is taken up and transported across this organ. Kajiwara et al (1996) showed that CH 3 Hg + is transported across the rat placenta by a neutral amino acid carrier in a time-and dose-dependent manner. These investigators demonstrated that co-injection with methionine increased the uptake of CH 3 Hg + .…”
Section: Molecular Mimicry and The Transport Of Ch 3 Hg + In Placentamentioning
confidence: 99%
“…This conjugate may then mimic methionine at the site of system L to gain access to the placenta. Accordingly, the authors concluded that the neutral amino acid carrier, system L (Kajiwara et al, 1996), mediated the uptake of CH 3 Hg + in placenta. The exact species of CH 3 Hg + that was transported was not determined in this study, nor was there direct evidence supporting the conclusion that system L was involved in this transport.…”
Section: Molecular Mimicry and The Transport Of Ch 3 Hg + In Placentamentioning
confidence: 99%